ØªØ·ÙˆÙŠØ± ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¨Ø¨Ø±Ù†Ø§Ù…Ø¬ ÙÙŠÙØ§ ÙÙŠØ¯ÙŠÙˆ Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø¨Ø© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø£Ù‡Ù„ÙŠØ© Ø±Ù…Ø¨Ø§ØªÙ† - Al Husna, Lathifah; Suharmon, Suharmon; Amrina, Amrina (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
This research aimed to develop arabic vocabulary learning media by using Viva Video Programme for the students of MTs Rambatan. The research used R & D method. While, development model used 4-D model: Define, Design, Develop without Disseminate. The result showed that the media of arabic vocabulary learning which is developed by using Viva Video can be used properly for the students of MTs Rambatan. According to the expert judgement, the developed media is valid, while the average score is 3.23.